2009
DOI: 10.2176/nmc.49.608
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Clear Cell Ependymoma of the Cerebellum From Hemangioblastoma by Thallium-201 Single Photon Emission Computed Tomography -Case Report-

Abstract: A 57-year-old man suffered from dizziness for about one year and truncal ataxia for about one month. Magnetic resonance imaging demonstrated a cystic tumor with a homogeneously enhanced mural nodule located in the cerebellar vermis. Computed tomography angiography revealed a hypervascular nodule. These findings were compatible with hemangioblastoma. Thallium-201 single photon emission computed tomography ( 201 Tl-SPECT) showed moderately high uptake in the early phase and moderately high retention in the delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Because of the rarity of this histological feature, we reviewed literature for previously reported cerebellar clear-cell [914] and intracranial tanycytic [1524] variant cases (Tables 1 and 2). However, the unique feature in this case—spindly bipolar cells surrounded by clear cells, forming cellular nests—was never described in any of these English-language studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the rarity of this histological feature, we reviewed literature for previously reported cerebellar clear-cell [914] and intracranial tanycytic [1524] variant cases (Tables 1 and 2). However, the unique feature in this case—spindly bipolar cells surrounded by clear cells, forming cellular nests—was never described in any of these English-language studies.…”
Section: Discussionmentioning
confidence: 99%
“…CCE is a rare brain tumor, accounting for 0.3% of all gliomas [9]. To date (and to our knowledge), only 27 reports in the English-language literature describe 69 cases [8, 9, 12, 2530]. CCE has a predilection for the supratentorial region compared with classical ependymoma subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The region of interest (ROI) of the lesion was manually placed over the area showing the greatest activity, and a normal brain parenchyma ROI was placed contralaterally. We calculated the early and delayed 201 Tl uptake ratios (TlE and TlD, respectively), and the RI was calculated as (TlE-TlD)/TlE (Nagamatsu et al 2009). Both the 67 Ga and 201 Tl studies demonstrated abnormal accumulation in the right cavernous sinus (Fig.…”
Section: Patient Presentationmentioning
confidence: 99%